The TGF-β inhibitory activity of antibody 37E1B5 depends on its H-CDR2 glycan. Issue 1 (2nd January 2017) - Tsui, Ping; Higazi, Daniel R.; Wu, Yanli; Dunmore, Rebecca; Solier, Emilie; Kasali, Toyin; Bond, Nicholas J.; Huntington, Catherine; Carruthers, Alan; Hood, John; Borrok, M. Jack; Barnes, Arnita; et al.
ABSTRACT: Excessive transforming growth factor (TGF)-β is associated with pro-fibrotic responses in lung disease, yet it also plays essential roles in tissue homeostasis and autoimmunity. Therefore, selective inhibition of excessive and aberrant integrin-mediated TGF-β activation via targeting the α-v family of integrins is being pursued as a therapeutic strategy for chronic lung diseases, to mitigate any potential safety concerns with global TGF-β inhibition. In this work, we reveal a novel mechanism of inhibiting TGF-β activation utilized by an αvβ8 targeting antibody, 37E1B5. This antibody blocks TGF-β activation while not inhibiting cell adhesion. We show that an N-linked complex-type Fab glycan in H-CDR2 of 37E1B5 is directly involved in the inhibition of latent TGF-β activation. Removal of the Fab N-glycosylation site by single amino acid substitution, or removal of N-linked glycans by enzymatic digestion, drastically reduced the antibody's ability to inhibit latency-associated peptide (LAP) and αvβ8 association, and TGF-β activation in an αvβ8-mediated TGF-β signaling reporter assay. Our results indicate a non-competitive, allosteric inhibition of 37E1B5 on αvβ8-mediated TGF-β activation. This unique, H-CDR2 glycan-mediated mechanism may account for the potent but tolerable TGF-b activation inhibition and lack of an effect on cellular adhesion by the antibody.